2020
DOI: 10.3390/ijms21030708
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Progress of Isolation, Culture, Storage, and Clinical Application of Human Bone Marrow Mesenchymal Stem/Stromal Cells

Abstract: Bone marrow mesenchymal stem/stromal cells (BMSCs), which are known as multipotent cells, are widely used in the treatment of various diseases via their self-renewable, differentiation, and immunomodulatory properties. In-vitro and in-vivo studies have supported the understanding mechanisms, safety, and efficacy of BMSCs therapy in clinical applications. The number of clinical trials in phase I/II is accelerating; however, they are limited in the size of subjects, regulations, and standards for the preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 193 publications
(216 reference statements)
1
77
0
Order By: Relevance
“…Currently, the role of BM-MSCs in colorectal cancer remains in dispute. 28 Human BM-MSCs were found to stimulate invasion, survival and tumorigenesis of colorectal cancer through the release of soluble neuregulin 1 (NRG1), activating the HER2/HER3-dependent PI3K/AKT signalling…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the role of BM-MSCs in colorectal cancer remains in dispute. 28 Human BM-MSCs were found to stimulate invasion, survival and tumorigenesis of colorectal cancer through the release of soluble neuregulin 1 (NRG1), activating the HER2/HER3-dependent PI3K/AKT signalling…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Previous studies have demonstrated the success of BM-MSCs for the treatment of hematopoietic pathologies, musculoskeletal diseases, immune disorder diseases, neurodegenerative diseases, cardiovascular disorders, sporty injuries, and other diseases of the gastrointestinal and integumentary systems. 27 Under long-term expansion, BM-MSCs may undergo senescence and transformation that contribute to tumor development and metastasis, 28 and a recent study reported that BM-MSCs promoted lung cancer growth and metastasis. 29 However, the role of rat BM-MSCs in the biological behaviors of colorectal CSCs remains unclear until now.…”
Section: Introductionmentioning
confidence: 99%
“…BMSCs have been proposed to be promising candidates for the treatment of various diseases, such as muscle, bone and cartilage diseases; blood-related diseases; immune system diseases; nervous system diseases; and injuries [23]. Recently, it was identi ed that BMSCs exert their therapeutic activity through a paracrine effect mediated by the release of small extracellular vesicles (EVs) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow (BM)-derived MSCs are non-HSCs located in the medullary stroma of bone marrow. BM-MSCs were discovered by Friedenstein et al in 1976 (25). Typically, they are extracted from iliac, femur, tibia, and sternum bone.…”
Section: Msc Tissue-derived Mscsmentioning
confidence: 99%